(untitled) (Baghdad Science Journal, 2014)
The objective of this study is to evaluate the level of cytokines IL-1?, IL-10 and IL-17A in the serum of patients with Alzheimer’s disease (AD), vascular dementia (VD) and down syndrome (DS). The results showed that Serum level of IL-1? was significantly increased in AD patients (3.79 ± 0.26 pg/ml) as compared with DS patients (2.78 ± 0.39 pg/ml) or controls (2.78 ± 0.22 pg/ml), while no significant difference was observed between AD and VD (3.25 ± 0.20 pg/ml) patients or between VD patients, DS patients and controls. The serum level of IL-10 was approximated in VD and DS patients and controls (3.39 ± 0.24, 2.77 ± 0.39 and 3.41 ± 0.35 pg/ml, respectively), but was significantly (P ? 0.05) increased in AD patients (5.73 ± 0.55 pg/ml) as compared to these groups. The serum level IL-17A was significantly increased in AD and VD patients (6.28 ± 0.35 and 5.32 ± 0.42 pg/ml, respectively) as compared with DS patients (3.75 ± 0.40 pg/ml) or controls (4.05 ± 0.28 pg/ml).IL-10 is important to diffrentiation between AD and VD.